Data from: Failure to coordinate management in transboundary populations hinders the achievement of national management goals: the case of wolverines in Scandinavia - Gervasi, Vincenzo (Data Archiving and Networked Services (DANS), 2019)
1. Large carnivores are expanding in Europe, and their return is associated with conflicts that often result in policies to regulate their population size through culling. Being wide-ranging species, their populations are often distributed across several jurisdictions, which may vary in the extent to which they use lethal control. This creates the conditions for the establishment of source-sink dynamics across borders, which may frustrate the ability of countries to reach their respective management objectives. 2. To explore the consequences of this issue, we constructed a vec-permutation projection model, applied to the case of wolverines in south-central Scandinavia, shared between Norway (where they are culled) and Sweden (where they are protected). We evaluated the effect of compensatory immigration on wolverine population growth rates, and if the effect was influenced by the distance to the national border. We assessed to what extent compensatory immigration had an influence on the number of removals needed to keep the population at a given growth rate. 3. In Norway the model estimated a stable trend, whereas in Sweden it produced a 10% annual increase. The effect of compensatory immigration corresponded to a 0.02 reduction in population growth rate in Sweden and to a similar increase in Norway. This effect was stronger closer to the Norwegian-Swedish border, but weak when moving away from it. An average of 33 wolverines were shot per year in the Norwegian part of the study area. If no compensatory immigration from Sweden had occurred, 28 wolverines shot per year would have been sufficient to achieve the same goal. About 15.5% of all the individuals harvested in Norway between 2005-2012 were compensated for by immigrants, causing a decrease in population growth rate in Sweden. 4. Synthesis and applications. When a population is transboundary, the consequences of management decisions are also transboundary, even though the political bodies in charge of those decisions, the stakeholders who influence them, ...